Manajemen Bimbingan Karier dalam Upaya Mewujudkan Kesiapan Kerja Siswa SMK Negeri 2 Yogyakarta - Christianus Aditya Kurniawan; Mundilarno Mundilarno (Universitas Sarjanawiyata Tamansiswa, 2023)
Abstract: The aims of the research include (1) to analyze how career guidance management works in an effort to realize the work readiness of students at SMK Negeri 2 Yogyakarta, (2) to analyze the supporting and inhibiting factors of career guidance management in an effort to realize the work readiness of students at SMK Negeri 2 Yogyakarta. (3) To analyze how the effectiveness of career guidance management is in an effort to realize the work readiness of students at SMK Negeri 2 Yogyakarta. The type of research used is qualitative with a descriptive approach, in order to be able to analyze how the description of the facts that occur regarding career guidance management at SMK Negeri 2 Yogyakarta. Data collection techniques in this study used interviews, observation, and documentation with research subjects of school principals, PPKS coordinators (Student Career Development Centers), guidance and counseling teachers and students. The data analysis technique used consists of data reduction by selecting raw data to become information, data presentation, namely presenting data in the form of descriptions, charts or tables, and drawing conclusions by making conclusions from research results referring to the problem formulation. The technique of checking the validity of the data uses triangulation of sources and techniques. Career guidance management planning at SMK Negeri 2 Yogyakarta has been going well, with the planning stages consisting of needs assessment, budget adjustment, preparation, preparation of career guidance management program. The organization of career guidance management has also been carried out properly through the determination and division of each task according to their competence and authority. The implementation of career guidance management at SMK Negeri 2 Yogyakarta has been going well for students from class X to class XII, with programs implemented at school and outside school. And supervision has also been going well with reviews that are summarized on an ongoing basis so that it can become a benchmark for further activities to be even better.